Chapter Dal lezionario all'aprakos. La versione liturgica dei vangeli greci e la tradizione testuale slava - Alberti, Alberto (Biblioteca di Studi Slavistici, 2018)
The textual tradition of the Slavic Gospels shows clear evidence of reciprocal influence between the liturgical version and the continuous text. The present survey analyzes 17 'textual nodes' of the Gospel of John, i.e. segments of the text for which the variants of 126 Greek lectionaries from the 8th-11th century have been collected. This analysis aims to shed light on a scarcely studied aspect of Slavic textual history, thus completing the picture outlined in previous works of the author, which were focused on the relationship with the tradition of Greek Tetraevangelia.